Hands-On Vision and Behavior for Self-Driving Cars : Explore Visual Perception, Lane Detection, and Object Classification with Python 3 and OpenCV 4. - Venturi, Luca (Packt Publishing, Limited, 2020)
This book will give you insights into the technologies that drive the autonomous car revolution. To get started, all you need is basic knowledge of computer vision and Python.
Keywords: Automated vehicles -- Computer programs.; Computer vision.; Python (Computer program language); OpenCV (Computer program language); elektronické knihy; electronic books